2022
DOI: 10.3390/s22155532
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Develop Chatbots for Assisting the Teaching and Learning Process

Abstract: Recently, in the commercial and entertainment sectors, we have seen increasing interest in incorporating chatbots into websites and apps, in order to assist customers and clients. In the academic area, chatbots are useful to provide some guidance and information about courses, admission processes and procedures, study programs, and scholarly services. However, these virtual assistants have limited mechanisms to suitably help the teaching and learning process, considering that these mechanisms should be advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 61 publications
0
41
0
1
Order By: Relevance
“…Both the learning buddy chatbot and the goal setting Chatbot employing Google Dialogflow were visual development tools that did not require prior computer programming knowledge (cf. Mendoza et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both the learning buddy chatbot and the goal setting Chatbot employing Google Dialogflow were visual development tools that did not require prior computer programming knowledge (cf. Mendoza et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, using blogs was useful and positive in learning ESP especially in developing the learners' classroom communication and in improving learners' autonomous and independent learning (Chong, 2010). Similarly, a designed model for developing a chatbot was assessed and it was found that the chatbot was useful as an extra tool to carry out academic and administrative tasks and facilitate communication between students and academic staff (Mendoza et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The steps of the prototype model are: 1. Researchers will collect the data needed in the process of making tools, and this stage is also the first step to find a problem formulation related to how to design a Robot (T-BOT) as an effort to overcome speech disorders in children (Mendoza et al, 2022). 2.…”
Section: Methodsmentioning
confidence: 99%